ChemInform Abstract: Reagent‐Free Synthesis of 2, 3, 4‐Polysubstituted Tetrahydroquinolines: Application to the Formal Synthesis of (.+‐.)‐Martinellic Acid and Martinelline. Issue 47 (4th November 2013) - Rong, Zhouting; Li, Qingjiang; Lin, Wenhan; Jia, Yanxing
Abstract A simple method is elaborated for the preparation of tetrahydroquinolines (III) from anilines (I) and aldehydes (II).